Earnings management prediction (a study of company’s life cycle) - Zamrudah, Rikazh; Riza Salman, Kautsar (Universitas Hayam Wuruk Perbanas, 2013)
This research aims to test whether deferred tax expense and accruals affect in detectingearnings management to avoid reporting earnings decline and to avoid reportinglosses at the stage of the company life cycle period from 2000 to 2007. Earnings managementis an effort made by the manager with the purpose to increase or decrease theprofit. Deferred tax expense is the expense arising from temporary differences betweenaccounting income and taxable income. The accrual is to recognize revenue when it isgenerated and recognized expense in the period incurred, regardless of the time ofreceipt or payment of cash. The life cycle is divided into stages of company, namelystart-up, growth, mature and decline. Results of this research is that there is no effectof deferred tax expense in detecting earnings management in order to avoid reportingearnings decline and to avoid reporting losses for the growth and mature stage of.Accrual has no effect in detecting earnings management to avoid reporting earningsdecline in both growth and mature stage. To avoid reporting losses, accruals in detectingearnings management influence the growth stage, while the mature stage accrualdoes not affect in detecting earnings management. This research does not test on startupstage and decline because the data sample is not sufficient for a stage to be tested.